OP01 High prevalence rates of unaddressed cardiometabolic risk and multi-morbidity in patients with non-alcoholic fatty liver disease. (20th September 2022) - Ginige, Ashan; Allen-Griffiths, Sarah; Healy, Katie; Matthews, Carol; Sieberhagen, Cyril; Cuthbertson, Daniel; Hydes, Theresa
Abstract : Introduction: Obesity, type 2 diabetes (T2D) and hypertension are risk factors for fibrosis in patients with Non-Alcoholic Fatty Liver Disease (NAFLD). NAFLD is also an independent risk factor for cardiovascular disease (CVD) and chronic kidney disease (CKD). As such screening for metabolic risk factors and extrahepatic manifestations of NAFLD has been incorporated into newly developed NAFLD care bundles. Aim: To examine the burden of metabolic disease and assessment and management of cardiometabolic risk in patients with NAFLD, and referral rates to other secondary care clinics. Methods: We performed a retrospective cohort study of patients with NAFLD seen in specialist hepatology clinics at a university hospital from February-September 2019. Patients were identified with a diagnosis of NAFLD using Fibroscan datasets. Data was extracted from existing electronic health records from primary and secondary care and examined in SPSS. Results: We identified 88 patients with NAFLD (mean age 55 years, 21.6% had cirrhosis). The prevalence of metabolic disease in patients with NAFLD (determined via all available primary/secondary care records and bloods results) is demonstrated in table 1 . 19% of patients had known CVD and 11% had CKD. 73% of NAFLD patients were seen in non-liver outpatient clinics (18% cardiology, 17% respiratory, 12% diabetes, 10% rheumatology, 68% other). Regarding metabolic assessment in secondary care, 68.2% had a weight documented, 11.4% had a documented body mass index, 4.5% had a blood pressure measurement taken in clinic and 15.5% and 9.1% had an HDL or triglyceride level requested from clinic or taken 6 months prior. No patients had a urine albumin creatinine ratio requested from clinic or a documented Q-risk score. 10% were referred to weight loss services. For patients with T2D the mean HbA1c was 56 mmol/mol (range 34–101) with 53.2% (n=25) having an HbA1c>48 mmol/mol. 70.2% were prescribed a glucose-lowering agent, 69.7% of this group were prescribed metformin alone; just 18.2% were prescribed >1 agent and 12.1% had been prescribed a newer glucose-lowering drug. Only 23.6% of patients were prescribed a statin. Conclusions: Weight loss and rigorous cardiometabolic risk management remain the cornerstones of NAFLD management, yet we demonstrate these factors are not rigorously assessed or controlled in the absence of a dedicated metabolic liver disease clinic. The introduction of metabolic liver disease care bundles are likely to enhance quality of clinical care. High rates of attendance at other secondary care clinics indicate that multidisciplinary team meetings and input may be beneficial in complex cases.